Shoot First: Stone Barrington #45 - Woods, Stuart (New York : G.P. Putnam's Sons, 2018)
"The irresistible Stone Barrington returns for another racy adventure from #1 New York Times-bestselling author Stuart Woods. Stone Barrington has faced intrigue before and come out clean on the other side, but this latest turn of events might be too scandalous even for him"--.
Keywords: Barrington, Stone (Fictitious character) -- Fiction; Private investigators -- Fiction; FICTION / Action & Adventure; FICTION / Suspense; FICTION / Thrillers; Suspense fiction; Adventure fiction